POLG p.A962T Mutation Leads to Neuronal Mitochondrial Dysfunction That is Restored After Mitochondrial Transplantation - Hu, W; Shi, C; Guo, H; Zhang, B (Physiological research, 2024)
Mutations in DNA polymerase gamma (POLG) are known as the predominant cause of inherited mitochondrial disorders. But how these POLG mutations disturb mitochondrial function remains to be determined. Furthermore, no effective therapy, to date, has been reported for POLG diseases. Using differentiated SH-SY5Y cells, a human neuronal model cell line, the current study investigated whether the novel POLG variant p.A962T impairs mitochondrial function. This involved quantifying mitochondrial DNA (mtDNA) content using PCR and assessing the expression levels of the subunits of complex IV (COXI-IV), a complex I subunit NDUFV1 and Cytochrome C (Cyto C) release using Western blotting. Activities of mitochondrial complex I, II, and IV were measured using colorimetric assays. Mitochondrial membrane potential (delta Psim) and ATP were evaluated using fluorescence assays and luminescent assays, respectively. In addition, we investigated whether mitochondrial transplantation (MT) using Pep-1-conjugated mitochondria could compensate for mitochondrial defects caused by the variant in cells carrying mutant POLG. The results of this study showed that POLG p.A962T mutation resulted in mitochondrial defects, including mitochondrial DNA (mtDNA) depletion, membrane potential (delta Psim) depolarization and adenosine triphosphate (ATP) reduction. Mechanistically, POLG mutation-caused mtDNA depletion led to the loss of mtDNA-encoded subunits of complex I and IV and thus compromised their activities. POLG p.A962T mutation is a pathogenic mutation leading to mitochondrial malfunction and mtDNA depletion in neurons. Cell-penetrating peptide Pep-1-mediated MT treatment compensated for mitochondrial defects induced by these POLG variants, suggesting the therapeutic application of this method in POLG diseases.
Keywords: Neurons; nádorové buněčné linie; DNA polymeráza gama; mitochondrie; DNA-Directed DNA Polymerase; mutace; Mitochondrial Diseases; DNA, Mitochondrial; Cell Line, Tumor; membránový potenciál mitochondrií; DNA Polymerase gamma; Mutation; Humans; mitochondriální DNA; neurony; DNA-dependentní DNA-polymerasy; Mitochondria; Membrane Potential, Mitochondrial; lidé; mitochondriální nemoci